Ability to Retension Knotless Suture Anchors: A Biomechanical Analysis of Simulated Bankart Lesions. Issue 6 (16th June 2022) - LeVasseur, Matthew R.; Mancini, Michael R.; Williams, Nicholas; Obopilwe, Elifho; Cote, Mark P.; Coyner, Katherine J.; Arciero, Robert A.; Caldwell, Paul E.; Mazzocca, Augustus D.
Background: Knotless suture anchors are gaining popularity in arthroscopic glenohumeral labral repairs. The ability to retension knotless designs after initial anchor placement has been reported; however, no studies have quantified this claim or investigated the biomechanical consequence of retensioning. Purpose/Hypothesis: To determine whether knotless and knotted suture anchors have biomechanical or anatomic differences with regard to labral repairs and to determine whether retensioning of knotless suture anchors affects capsular tension, labral height, and capsular shift. We hypothesized that retensioning of knotless anchors would result in improved capsular tension compared with conventional knotted suture anchors. Study Design: Controlled laboratory study. Methods: A total of 18 fresh-frozen cadaveric shoulders with a mean age of 56 years were dissected to the capsule and disarticulated at the humeral capsular insertion. The scapula was potted and placed in a custom shoulder simulator to tension the capsule via braided sutures localized to the anteroinferior glenohumeral ligament. Specimens were randomized into 3 groups: (1) Knotted (KT), (2) Knotless with end retensioning (KLend ), and (3) Knotless with stepwise retensioning (KLstepwise ). All repairs were completed using all-suture anchors placed at the 5-, 4-, and 3-o'clock positions. KLstepwise was used to simulate an intraoperative technique. Resultant mean capsular tension under 5 mm of displacement (subfailure loading) was measured for each anchor placement and retensioning step. Labral height and capsular shift were measured using a MicroScribe digitizer. Results: The intact, defect, 1-anchor, 2-anchor, and 3-anchor tensions were not significantly different between the KT and KLend groups. For the latter, retensioning of all knotless anchors increased capsular tension by 2.1 N compared with its 3-anchor state, although this was not statistically significant ( P = .081). The KLstepwise group explored an alternative method to retension the capsule using knotless anchors, with similar final capsular tensions compared with the other groups. All repairs had similar improvements in capsulolabral height and superior capsular shift. Conclusion: Knotted and knotless suture anchors provided similar overall restorations in anteroinferior glenohumeral ligament tension. However, knotless devices were capable of small but statistically insignificant improvements in capsular tension with retensioning. Clinical Relevance: Retensioning of knotless anchors allows the surgeon to tighten regions of the glenohumeral capsule that remain lax after repair.